Moby Dick [videorecording (DVD)] - Peck, Gregory, 1916-2003; Basehart, Richard, 1914-1984; Welles, Orson, 1915-1985; Huston, John, 1906-1987; Melville, Herman, 1819-1891 (MGM Home Entertainment, 2001)
Consumed by an insane rage, Captain Ahab has but one purpose in life-- revenge on the great white whale who maimed and disfigured him.